Covid-19 mimicking breast cancer progression - Kufel-Grabowska, Joanna; Mozer-Lisewska, Iwona; Cholewiński, Witold; Bartoszkiewicz, Mikołaj; Litwiniuk, Maria (Medycyna Paliatywna/Palliative Medicine, 2021)
In February 2019, a 73-year-old woman reported with a tumour of the right breast and enlarged lymph nodes in the right axilla. A core-needle biopsy of the tumour was performed, which confirmed the diagnosis of invasive breast carcinoma NST G2, oestrogen-dependent, HER2-negative; ki 67 was 2%. Imaging showed metastases in the lungs and liver, and numerous osteolytic lesions in the bones. The patient was qualified for ribociclib therapy in combination with letrozole and zoledronic acid, and she received palliative irradiation of Th6-Th8 and Th12-L2. The treatment stabilized the cancer and the patient’s general condition by February 2020. In a PET scan performed at that time previously unobserved lymph nodes in the mediastinum and liver recess were described; the lesions were ambiguous. In July 2020, there was progression of metastatic changes in the lymph nodes. CDK4/6 inhibitor and letrozole were discontinued, tamoxifen was included, and zoledronic acid therapy was continued. After the treatment change there was a rapid deterioration of the patient’s general condition; she patient was drowsy and confused. The spread of cancer to the central nervous system (CNS) was suspected. The patient’s husband and daughter (physicians) were diagnosed with a coronavirus infection. The patient’s test was also positive; thus, she was referred to the infectious diseases ward. The dominant symptom was progressive weakness, followed by neurological symptoms: confusion, dizziness, and disinhibition reaction. Her general condition did not allow CNS imaging diagnostics. During hospitalization the patient was treated symptomatically, but her general condition did not improve. The patient died after 16 days of hospitalization.